Prevalence of Thyroid disorders in Nasiriya City, Iraq - Zoori, Ammani; Mousa, Hind (University of Thi-Qar Journal of Science, 2023)
Thyroid disorders are the second biggest endocrine problem in society after diabetes. Environmental and genetic factors lead to the development of thyroid disorders. So this study was designed to determine the prevalence of thyroid disorders in Nasiriya City. One hundred-twenty subjects of both genders were involved in this study 80 of whom were patients, and 40 were healthy people. A blood sample and personal information were collected from all. The levels of thyroid hormones were estimated by the Cobas e411 electrochemiluminescence immunoassay (ECLI). The study found that the incidence of females was more than males (77.5%, 22.5%) and the ratio was 3.4:1. The results showed hypothyroidism disorder was more prevalent than hyperthyroidism and (83.64%) of hypothyroidism were female, and only (16.36%) were male, also (64%) of hyperthyroidism were female while male represented only (36%) of them. The majority of patients were aged 35-46 years. The results indicated that (43.75%) of patients had a family history, (26.25%) were diagnosed with hypothyroidism, and (17.5%) were diagnosed with hyperthyroidism. It was concluded that thyroid disorders, especially hypothyroidism, constitute a serious concern for public health, and middle-aged people and females were the categories most susceptible to thyroid disorders.